BOOK REVIEW: MULTIMODALITY IN ENGLISH LANGUAGE LEARNING - Sugianto, Ahmad (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2023)
Multimodality has been one of the prominent and burgeoning fields and phenomena in English classrooms. It is based on both the credence which is proven by scholarly evidence that English language learning and instruction will be significantly and effectively delivered if more than one semiotic resource or mode is used. Lots of scholars across the globe have taken part in portraying such significance and effectiveness of multimodality concerning English classrooms. Diamantopoulou and Ørevik (2022) have conflated sheer studies from various distinguished authors providing ‘fresh’ outlooks of the use of multimodality, particularly in English as an additional language (EAL) context across the globe. The use of multimodality in EAL is concisely discussed from various lenses, from its salient perspectives, and pedagogical practices through assessments. Thus, this book is recommended to those who are concerned and willing to capture the latest trajectories of the use of multimodality pertaining to EAL by its par excellence as well as the matter at hand.